PENGARUH PENGAWASAN GURU TERHADAP KEDISIPLINAN SISWA SMPN 1 KUANTAN HILIR KABUPATEN KUANTAN SINGINGI - Wiyona Efrianti Ariastu; Gimin Gimin; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was motivated by concerns about students who began to violate school discipline, especially discipline. Attitudes that are not in accordance with this order are the result of environmental influences that can damage students' discipline. So it takes the supervision of teachers who can shape student discipline and attitudes that can build discipline towards discipline so that students better understand the meaning of discipline. The formulation of the problem in this study is how does the influence of teacher supervision on discipline. As for the population, all the teachers numbered 30 people. By using a saturated sampling technique, 30 teachers were selected as samples in this study. Data collection techniques are carried out through observation, questionnaires, interviews and documentation. In analyzing the data using simple linear regression analysis. Descriptive results of teacher supervision given by Kuantan Hilir 1 Junior High School teacher in Kuantan Singingi District, which is 85% in very good category. And the descriptive results of student discipline at 81% in the excellent category. Descriptively the supervision of the teacher towards the discipline of influential students is very good. The results of this study indicate that there is an influence of teacher supervision on the discipline of students in the Kuantan Hilir 1 Junior High School in Singingi Regency. this is evidenced by a series of simple linear regression tests between variables X and Y variables, obtained Fcount = 21.305 and Ftable 4.20 obtained from the study of a list of F distributions with N = 30, at a significant level of 5%, thus Fcount> Ftable or 21,305> 4,20, then H0 is rejected and Ha is accepted as meaning significant, there is an influence of teacher supervision on discipline of students of Kuantan Hilir 1 Junior High School Singingi Regency Key Words: Teacher Supervision, Discipline